Formação de professores : um diálogo com a psicologia educacional - Souza, Helen Santana Mangueira de (2015)
The initial teacher training model through the undergraduate courses requires constant reflection and questioning. Among the pedagogical disciplines that constitute the undergraduate courses there is the Educational Psychology. As a psychologist, I understand that Psychology can be one of the bases for the teaching practice. By observing the teacher training model in Brazil, which has always prioritized specific disciplines at the expense of pedagogical training on teaching, and finding out that the researches about Psychology in teacher‘s education are still weak in Brazil, the problem of this research arose: How do teachers UFMT / CUR analyze the influence of Psychology in their training? Thus, the objective of this study was to analyze the understanding that students from UFMT / CUR Languages, Geography, History, Biology and Mathematics degrees have about Educational Psychology in their training. Using the methodological design based on the principles of historical and dialectical materialism, five UFMT / CUR students, that were working as a teacher, graduated in the period 2010-2013, one representative of each degree course (Languages, Geography, Biology, History and Mathematics ), took part in the survey. As instrument for data collecting on the research problem, the Plans of Educational Psychology Discipline were analyzed and the Pedagogical Projects of the courses and were also made semi-structured interviews carried out from a dialogical perspective. What was possible to notice is that the training of teachers through the degrees in UFMT / CUR has prioritized the formation of bachelor instead of training of the teacher‘s program, repeating the model of teacher training 3 + 1 set in the nineteenth century, where they were offered three years of training with a bachelor's degree, plus one year for the formation of licensed. It was also noticed, that remains in the teachers' ideas a clinical model of psychologist's performance, heritage training of these professionals throughout history. It was observed that the classes were extremely theoretical, some related to the practice, and also that there was no theoretical appropriation by licensed. It was found also that the presence of Educational Psychology in teacher education influenced licensed toward the listening and the need to respect and understanding of the student, however, in a individualized and decontextualized focus. Thus, further studies should be conducted to a better understanding of the proposed theme, towards a performance that allows the humanization and human emancipation.